Rāingān kānwičhai r̄ưang kānwikhr̨o tonthun læ phont̨̄opth̄æn čhāk kānlongthun plūk klūai h̨̄om nai Čhangwat ʻAyutthayā - Dūangrat Phōnḡœn (Khana Witthayā Kānčhatkān, Sathāban Rātchaphat Phra Nakh̨̄on Sī ʻAyutthayā, 1998)
Studies on the cost and benefit from investment in planting fragant bananas in Phra Nakhon Si Ayutthaya, Central Thailand.